Analysis Of The Physical Environment Of Homes And Healthy Living Behavior On Tuberculosis Sufferer In The Working Area Of Singosari Health Center, Malang District - Vivi Ilmi Habasithoh; Ukik Agustina (Indonesian Journal of Nutritional Epidemiology and Reproductive, 2024)
The incidence of tuberculosis cases in Indonesia is 354 per 100,000 population. In Malang Regency, in the first 3 months of 2023, 618 people were infected with tuberculosis. In the Singosari Health Center work area in 2023, there were 60 people who tested positive for tuberculosis. Generally, transmission occurs indoors where sputum droplets are present for a long time. Ventilation can reduce the number of droplets, while direct sunlight can kill germs. Unmaintained healthy living behavior can increase disease transmission considering that tuberculosis is an infectious disease that is transmitted through droplets or air. The purpose of this study was to determine the relationship between the physical environment of the home and PHBS with the incidence of tuberculosis. The design of this study is case control, this type of study moves from the effect (disease) namely tuberculosis to the cause (exposure) namely the physical environment of the home and PHBS. The study population was divided into a case group (tuberculosis sufferers) and a control group (not tuberculosis sufferers). The sample size was calculated using the Lemeshow formula until a sample of 20 cases and 20 controls were obtained. The sampling method used is the simple random sampling method. The independent variables of this study are the physical environment of the house and PHBS while the dependent variable is the incidence of tuberculosis. The research instrument used a questionnaire, roll meter, lux meter and hygrometer. Data analysis used the chi-square test. The results of the statistical test at α = 0.05 showed that the variables of the physical environment of the house that had a significant relationship with the incidence of tuberculosis were ventilation area (p = 0.004), lighting (p = 0.002) and humidity (p = 0.003). At α = 0.05 the analysis test showed that there was a relationship between PHBS and the incidence of tuberculosis (p = 0.001). The physical environment of the house (ventilation area, lighting and humidity) and PHBS have been proven to have a relationship with the incidence of tuberculosis so that they need to be considered and applied in everyday life in order to reduce the risk factors for transmission. It is hoped that the community will pay attention to the construction of the house, if not possible, a healthy house can be attempted by implementing good and correct PHBS.developed until the intervention of the behavior of adolescent girls toward anemia prevention.